Systematics of Amphineurus (Rhamphoneurus Alexander) (Diptera: Tipuloidea: Limoniidae) - Daubian Santos; Rodrigo dos Reis Santos; Guilherme Cunha Ribeiro (Arthropod Systematics & Phylogeny, 2022)
The subgenus Amphineurus (Ramphoneurus Alexander) (Diptera: Limoniidae), a group of craneflies endemic to southern South America, is revised. The previously described species are redescribed and illustrated, along with fifteen new species: A. (R.) alexanderi sp. nov., A. (R.) amorimi sp. nov., A. (R.) anchoralis sp. nov., A. (R.) anfractus sp. nov., A. (R.) billinghami sp. nov., A. (R.) caleuchus sp. nov., A. (R.) deceptus sp. nov., A. (R.) falcatus sp. nov., A. (R.) immaculatus sp. nov., A. (R.) morphyi sp. nov., A. (R.) oosterbroeki sp. nov., A. (R.) podenasi sp. nov., A. (R.) theischingeri sp. nov., A. (R.) triangularis sp. nov., and A. (R.) stigmaticus sp. nov. In addition, A. (R.) fuscifusus Alexander is considered a nomen dubium. A phylogenetic analysis with a broad taxonomic sampling with all valid species of the subgenus A. (Rhamphoneurus Alexander) and species from all the subgenera of Amphineurus Skuse is performed. The broad outgroup sampling used in the study (including taxa from the entire range of distribution of Amphineurus) suggests that the subgenus A. (Rhamphoneurus) is a monophyletic taxon, that its closest relatives are taxa currently distributed in New Zealand, and that Australasian taxa are paraphyletic with respect to the Neotropical Clade.